Evaluating single-institution resource costs of consolidative radiotherapy for oligometastatic non-small cell lung cancer using time-driven activity-based costing. (July 2020) - Pezzi, Todd A.; Ning, Matthew S.; Thaker, Nikhil G.; Boyce-Fappiano, David; Gjyshi, Olsi; Olivieri, Nicholas D.; Guzman, Alexis B.; Incalcaterra, James R.; Mesko, Shane; Gandhi, Saumil; Chun, Stephen; Tang, Chad; et al.
Highlights: Consolidative radiotherapy (RT) has been shown to improve overall survival in oligometastatic non-small cell lung cancer (NSCLC). We quantified the costs of RT in oligometastatic NSCLC, by applying time-driven activity-based costing (TDABC). This analysis uses TDABC to estimate the relative internal costs of various RT strategies associated with treating oligometastatic NSCLC. This methodology will become increasingly relevant in context of the anticipated mandate of alternative/bundled payment models. Abstract: Background: Consolidative radiotherapy (RT) has been shown to improve overall survival in oligometastatic non-small cell lung cancer (NSCLC), as demonstrated by a growing number of prospective trials. Objective: We quantified the costs of delivery of consolidative RT for common clinical pathways associated with treating oligometastatic NSCLC, by applying time-driven activity-based costing (TDABC) methodology. Methods: Full cycle costs were evaluated for 4 consolidative treatment regimens: (Regimen #1) 10-fraction 3D conformal radiation therapy (3D-CRT) as palliation of a distant site; (#2) 15-fraction intensity-modulated RT (IMRT) to the primary thoracic disease; (#3) 15-fraction IMRT to the primary plus 4-fraction stereotactic ablative radiotherapy (SABR) to a single oligometastatic site; and (#4) 15-fraction IMRT to the primary plus two courses of 4-fraction SABR for two oligometastatic sites. Results: For each of the four treatment regimens, personnel represented a greater proportion of total cost when compared with equipment, totaling 61.0%, 65.9%, 66.2%, and 66.4% of the total cost of each care cycle, respectively. In total, a 10-fraction regimen of 3D-CRT to a distant site represented just 37.2% of the total cost of the most expensive course. Compared to total costs for 15-fraction IMRT alone, each additional sequential course of 4-fraction SABR imparted a cost increase of 43%. Conclusion: This analysis uses TDABC to estimate the relative internal costs of various RT strategies associated with treating oligometastatic NSCLC. This methodology will become increasingly relevant to each organization in context of the anticipated mandate of alternative/bundled payment models for radiation oncology by the Centers for Medicare and Medicaid Services.